Levels of Optimism: Differences Between Adults in Latin American Countries [Niveles de Optimismo: Diferencias Entre Adultos de Países Latinoamericanos] - Lavarello-Salinas, J; Espinoza-Guerrero, E (Pontificia Universidad Javeriana, 2017)
Dispositional optimism is the variable within Positive Psychology that has been studied in different environments, as it is presented as related and predictor of psychological variables and health environments. The present study investigated whether there were significant differences in Optimism levels measured through the Life Orientation Test (LOT-R) according to the country of residence of the people, in an accidental sample of 464 people from Argentina, Mexico and Chile. No significant differences were found in the Optimism dimension, but in the Pessimism dimension, where Argentina presents the highest levels. In addition, significant differences were detected in 2 of the items in the Optimism dimension, where Mexican residents presented themselves with better levels, and in an item of the dimension Pessimism. The results are limited to the study that was carried out but they emphasize the importance of carrying out more studies in subjects that the present governments are working to improve the quality of life of the people that can be directly influenced by positive variables like Optimism.